How to Design the Vietnam Labor Code to Improve Gender Equality - World Bank Group (World Bank, Hanoi, 2019)
Vietnam is in the process of updating its Labor Code of 2012. This advisory note is designed to inform a dialog on opportunities for how the 2012 Labor Code can be adjusted to balance the playing field between men and women so that they have equal access to and equal benefits from the labor market. It does so with to objective to support the gender assessment of new laws as stipulated by the Vietnam Promulgation of Laws of 2015. The advisory note draws on analysis carried out by the task team and under the World Bank’s Vietnam Jobs Diagnostic. This advisory note is follow-up to a workshop hosted by the Social Affairs Committee of the Vietnam National Assembly and The World Bank on January 11, 2019, for members of the Social Affairs Committee and other National Assembly representatives. After the workshop the Committee and Social Affairs Department of the National Assembly asked for a write up of the recommendation made at the workshop. The recommendations and the workshop were carried out as part of the Vietnam Women’s Economic Empowerment Project under the Australia-World Bank Group Strategic Partnership Program 2 (ABP2). The project is supporting the Government of Vietnam on its efforts to ensure that gender is addressed in legislation, including for example, the Labor Code.